2022
DOI: 10.5455/msm.2022.33.28-32
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Breast Cancer Risk: Our Experience and Mini-review of the Literature

Abstract: Background: According to data from World Health Organization, breast cancer constitutes the second most common diagnosed malignancy after lung cancer and the second leading cause of death among women in 2020, worldwide. The protective role of breastfeeding in the emergence of breast malignancy has been mentioned in several studies, indicating the important part it can have in the effort of reducing breast cancer’s incidence. Objective: To investigate a possible associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
4
0
2
Order By: Relevance
“…The most extensive pooled analysis from almost 50 studies, 30 studies showed an overall 4% reduction risk per 12 months of breast feeding for all parous women. 22 In the present study a significant reduction of the risk of developing breast cancer was observed among women whose total duration breast feeding was 2 years or more compared with women has less than one year of breast feeding or absent of breast feeding.…”
Section: (Table-ii)supporting
confidence: 51%
“…The most extensive pooled analysis from almost 50 studies, 30 studies showed an overall 4% reduction risk per 12 months of breast feeding for all parous women. 22 In the present study a significant reduction of the risk of developing breast cancer was observed among women whose total duration breast feeding was 2 years or more compared with women has less than one year of breast feeding or absent of breast feeding.…”
Section: (Table-ii)supporting
confidence: 51%
“…Hasil penelitian ini sejalan dengan yang penelitian yang dilakukan oleh Irfannur tahun 2021 bahwa dari 56 responden yang mempunyai riwayat menyusui 33 orang (15,3%) diantaranya merupakan penderita kanker payudara (14). Riwayat menyusui memiliki efek yang dapat mencegah terjadinya kanker payudara karena adanya penurunan jumlah hormon estrogen dan pengeluaran substansi karsinogenik selama masa menyusui (15).…”
Section: Cunclassified
“…Menyusui memiliki manfaat untuk mengurangi kadar hormon estrogen yang terdapat didalam payudara dan memiliki efek langsung, dimana substansi karsinogenik yang merusak DNA akan dikeluarkan dari jaringan saluran payudara, sehingga dapat mengurangi risiko terkena kanker payudara. Riwayat menyusui memiliki efek yang dapat mencegah terjadinya kanker payudara karena adanya penurunan jumlah hormon estrogen dan pengeluaran substansi karsinogenik selama masa menyusui (15).…”
Section: Cunclassified
“…Mastitis is a common and severe disease for humans and animals that increases the risk for breast cancer [ 17 , 18 ] and impairs milk yield and quality, making it a major threat to women's health and hindering the development of the dairy industry. Mounting evidence suggests a possible “microbiota-gut-mammary axis” in the context of mastitis as shown by gut dysbiosis initiating and facilitating the development of mastitis.…”
Section: Introductionmentioning
confidence: 99%